Roles of centre and states in disinvestment - Kaur, Simrit (2003)
The process of privatisation was begun with central public sector undertakings (PSUs) by partially disinvesting the shares in select enterprises. This continued from 1991 to 2000. However, since the sale of Modern Foods in 2000, every sale has been a strategic one. On the other hand, the states have gone in for partial disinvestments side by side with strategic sales, though the preference is for the latter. However, the states made strategic sales in a few enterprises much earlier in the 1980s, when the Centre had not even given a thought to divestitutre. Privatisation is appropriate where market failures are less serious than state failures. - Reproduced.
Keywords: Public sector; Privatization